Pengaruh Variabel Makroekonomi Terhadap Return Saham Sektor Keuangan di Indonesia - Nadia Etri Ningsih; Idris Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
The purpose of this study was to determine the effect of macroeconomic variables on stock returns in the financial sector in Indonesia. The indicators of macroeconomic variables studied were world gold price, exchange rates, inflation, an economic growth. This study uses secondary time series data from 2005 first quarter to fourth quarter 2019. The research data analysis method used is multiple linear regression analysis and Error Correction Model (ECM). The result oh this study indicate that : (1) the world gold price has a negative effect on the stock return of the financial sector in Indonesia; (2) the exchange rate has a negative effect on the stock return of the finacial sector in Indonesia; (3) inflation has a negative effect on stock return for the financial sector in Indonesia; (4) economic growth has a negative effect on the stock return of the finacial sector in Indonesia.